Educational Proposal for Health Promotion of the Worker of a Public Hospital in the State of Pará: Elaboration of a labor gymnastics protocol based on the pilates method (Research, Society and Development, 2022)
Introduction: The growth of work-related diseases has raised the interest of researchers in quality of life at work, with a strong relationship between worker - work environment and work - illness, in this context, the Gymnastics in the Workplace (WE) has been an alternative in the reduction and / or prevention of illness. Objective: the proposal of this study is the construction of an educational tool through a protocol with GL orientations from the Pilates Solo Method, that can positively impact on the improvement of the worker's health. Method: This is a quantitative descriptive study developed in two stages; Bibliographic survey in the databases (BVS/PUBMED/SCIELO) and the survey of the total number of servers components of multiprofessional teams of UCINCO/UCINCA of neonatology in a public teaching hospital (table 1), preparation and application of a questionnaire situational diagnosis, prepared using the tools available in Google Forms and based on Likert scale being sent a link to access the questionnaire to the target audience of the research through an access link via e-mail and WhatsApp, including in the study those who agreed with the TCLE. Of the 184 servers listed 94 answered the questionnaire and gave acceptance to the TCLE. Results: The questionnaire questions, being qualitative variables were represented as absolute and relative frequencies (percentages). After the analysis, the answers had a reliability index above 70% according to the Crombach alpha coefficient of 0.9137 and significance measured by the Pearson chi-square test for trend with p-value < 0.05, being favorable to the elaboration of an educational tool, through a protocol with orientation of labor gymnastics based on the Pilates method.